EFFECT OF BIOSTIMULATORS ON GROWTH AND DEVELOPMENT OF WHEAT (Multidisciplinary Journal of Science and Technology, 2024)
This article provides information about the factors necessary for the growth and development of wheat, one of the most important agricultural products of our country, and the effect of biostimulants on this growth and development.